Political Risk and Capital Flight - Quan Le; Paul J. Zak (Claremont McKenna College, Department of Economics, 2001)
Capital flight often amounts to a substantial proportion of GDP when developing countries face crises. This paper presents a portfolio choice model that relates capital flight to rate of return differentials, risk aversion, and three types of risk: financial risk, political risk, and policy risk. Estimating the equilibrium capital flight equation for a panel of 47 developing countries over 16 years, we show that all three types of risk have a statistically significant impact on capital flight. Quantitatively, political risk is the most important factor causing capital flight. We also identify several political factors that reduce capital flight by signaling market-oriented reforms are imminent.
Keywords: F3; P16; 330; capital flight; political risk; policy risk; portfolio choice